Inhaled medication for asthma management: evaluation of how asthma patients, medical students, and doctors use the different devices - Muniz, Janaína Barbosa [UNESP]; Padovani, Carlos Roberto [UNESP]; Godoy, Irma [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2003)
Asthma results from a combination of three essential features: airflow obstruction, hyperresponsiveness of airways to endogenous or exogenous stimuli and inflammation. Inadequacy of the techniques to use different inhalation devices is one of the causes of therapeutic failure. The main purpose of this study was to evaluate how 20 medical students, 36 resident physicians of Internal Medicine/Pediatrics, and 40 asthma patients used three devices for inhalation therapy containing placebo. All patients were followed at the Pulmonary Outpatient Service of Botucatu Medical School and had been using inhaled medication for at least six months. The following devices were evaluated: metered dose inhalers (MDI), dry powder inhalers (DPI), and MDI attached to a spacer device. A single observer applied a protocol containing the main steps necessary to obtain a good inhaler technique to follow and grade the use of different devices. Health care professionals tested all three devices and patients tested only the device being used on their management. MDI was the device best known by doctors and patients. MDI use was associated with errors related to the coordination between inspiration and device activation. Failure to exhale completely before inhalation of the powder was the most frequent error observed with DPI use. In summary, patients did not receive precise instruction on how to use inhaled medication and health care professionals were not well prepared to adequately teach their patients.

A asma resulta da combinação de três características essenciais: obstrução das vias aéreas, hiper-responsividade brônquica e inflamação. O uso dos inalantes com técnica inadequada tem sido apontado como um dos responsáveis pelo fracasso terapêutico. O objetivo deste estudo foi avaliar o domínio da técnica de uso das medicações inalatórias de 20 estudantes do 6º ano médico, 36 médicos residentes em Clínica Médica/Pediatria e de 40 pacientes. Os pacientes eram acompanhados no Ambulatório de Pneumologia do HC/Unesp e estavam em uso de medicação inalatória durante pelo menos seis meses. Os dispositivos avaliados foram: nebulímetros pressurizados (NEPS), nebulímetros com espaçadores (ESP) e inaladores de pó seco (IPS). A técnica foi observada e pontuada por examinador único, de acordo com protocolo apropriado. Os profissionais de saúde demonstraram a técnica com os três tipos de inalantes citados, enquanto os pacientes foram avaliados somente nos que faziam parte do seu tratamento. O NEP foi o dispositivo mais conhecido tanto por médicos quanto por pacientes. Para o NEP, os erros mais comuns, em todos os grupos estudados, foram os relacionados com a coordenação entre a inspiração e o acionamento do dispositivo. Para o IPS, foi a não realização da expiração máxima antes da inalação do medicamento. Foi observado que os pacientes apresentavam grande carência de informações precisas quanto ao uso dos dispositivos e que os profissionais desconheciam a técnica ou sentiam-se inseguros quanto à melhor forma de ensinar seus pacientes, optando, muitas vezes, por não orientá-los.
Inalantes no tratamento da asma: avaliação do domínio das técnicas de uso por pacientes, alunos de medicina e médicos residentes
Keywords: Asthma; Administration, inhalation; Techniques; Students, medical; Medical Staff, hospital; Asma; Administração por inalação; Técnicas; Estudantes de medicina; Médicos residentes